Social Media Mobility: Leveraging Twitter Networks in Online Diplomacy. Issue 2 (17th April 2020) - Manor, Ilan; Segev, Elad
Abstract: Recent years have seen mass adoption of social media by ministries of foreign affairs (MFAs). However, diplomats are still searching for ways to evaluate their online activity and assess the impact of online activities on offline diplomacy. This article argues that the centrality of a diplomatic institution to a Twitter network of its peer can be used to evaluate both online and offline diplomacy. Central actors on Twitter can set diplomats' offline agenda, influence how diplomats view issues being debated in diplomatic forums, gather information relevant to the policy formulation process and become information brokers between nations. Moreover, through a two‐year analysis of the Twitter networks of MFA and UN missions we demonstrate that diplomatic institutions can perform an act of upward social media mobility by which they become more central to Twitter networks. We also show that hard power resources such as the relative wealth of nations and their population size does not guarantee online centrality. Thus, diplomatic institutions may suffer from downward social media mobility in which they become less influential online. Finally, we identify a set of digital tactics and strategies that enable MFAs and embassies to become more central to Twitter networks of their peers. Abstract : From a strategic perspective, social media mobility requires that diplomats be trained in the use of social network analysis.